2014
DOI: 10.1111/pce.12258
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early Al‐responsive genes in rice bean (Vigna umbellata) roots provides new clues to molecular mechanisms of Al toxicity and tolerance

Abstract: Significant secretion of citrate from root apex of rice bean (Vigna umbellata) is delayed by several hours under aluminium (Al) stress. However, the molecular basis of regulation of VuMATE1, a gene encoding an Al-activated citrate transporter, remains unclear. In this study, we used suppression subtractive hybridization together with reverse northern blot analysis and qRT-PCR to identify genes with altered transcript levels in the root apex after treatment with low (5 μM) or high (25 μM) concentration of AlCl3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…On the basis of rice bean root tip Al stress-responsive suppression subtractive hybridization libraries (Fan et al, 2014), we obtained a full-length VuAAE3 cDNA via rapid amplification of cDNA ends (RACE)-PCR method (GenBank accession no. KX354978; Supplemental Fig.…”
Section: Cloning and Sequence Analysis Of Vuaae3 From Vigna Umbellatamentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of rice bean root tip Al stress-responsive suppression subtractive hybridization libraries (Fan et al, 2014), we obtained a full-length VuAAE3 cDNA via rapid amplification of cDNA ends (RACE)-PCR method (GenBank accession no. KX354978; Supplemental Fig.…”
Section: Cloning and Sequence Analysis Of Vuaae3 From Vigna Umbellatamentioning
confidence: 99%
“…The potential of formate formation from oxalate catabolism led us to hypothesize whether this pathway exist in rice bean. More interestingly, a gene previously named as peroxisomal-coenzyme A synthetase (PCAS) was found to be up-regulated significantly in root apices of rice bean, and actually PCAS has high amino acid sequence homology with Arabidopsis AAE3 (Fan et al, 2014). Thus, it is likely that one possible route to formate accumulation originates from degradation of oxalate mediated by PCAS.…”
mentioning
confidence: 99%
“…In this study, we isolated a full-length VuFDH cDNA, and found that the expression of VuFDH in rice bean root tips is enhanced greatly not only by Al (as previously shown; Fan et al, 2014) but also by low pH stress. We also showed that Al induces the rapid accumulation of formate in rice bean root apices, an accumulation that may contribute to Al-induced root growth inhibition.…”
mentioning
confidence: 96%
“…For example, transcriptional profiling studies revealed that genes related to metabolism were differentially expressed in response to Al stress in Arabidopsis, rice (Oryza sativa), barrel clover (Medicago truncatula), maize (Zea mays), and rice bean [Vigna umbellata; Chandran et al, 2008;Kumari et al, 2008;Fan et al, 2014;Mattiello et al, 2014;Wang et al, 2014)]. In addition, proteomic analysis has indicated that proteins of metabolic function are differentially regulated in response to Al stress in roots of tobacco, soybean (Glycine max), and rice (Zhou et al, 2009;Zhen et al, 2007;Wang et al, 2014).…”
mentioning
confidence: 99%
“…18,21 Either AtSTOP1 and AtSTOP2 in Arabidopsis or OsART1 in rice is constitutively expressed, 14,16,17 thus Al or H C regulates them posttranslationally, e.g. direct activation of protein activity.…”
Section: Transcriptional Regulation Versus Activationmentioning
confidence: 99%